Sosialisasi Artifical Intelligence Menuju Smart Government Untuk Kelompok Pkk Rw 06 Tegal Parang Mampang - Riana Dwiza; Subekti Agus; Putra Zico Pratama; Pardede Hilman Ferdinandus; Faruq Aziz (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2023)
The rapid advancement of Artificial Intelligence (AI) technology has significantly impacted industries and government sectors during the fourth industrial revolution. AI offers the potential to simplify and streamline public service delivery, enabling governments to enhance service quality, build public trust, and improve efficiency. In Indonesia, the Women's Empowerment Family Welfare Movement (PKK) plays a crucial role in promoting women's participation in national development. As partners to village and sub-district governments, PKK supports population management and regional development. In line with its commitment to Community Service, Nusa Mandiri University organized the Socialization of Artificial Intelligence Towards Smart Government for PKK RW 06 Tegal Parang Mampang. The main objective of this activity was to inform the management of PKK RW 06 about the benefits and implementation of AI technology in achieving smart government and enhancing PKK's services and activities. The socialization event, attended by 12 participants, was conducted in a hybrid format, combining face-to-face meetings and digital technology. The participants exhibited great enthusiasm in grasping the material and actively engaging in interactive Q&A sessions. As a result of the socialization, participants demonstrated an improved understanding of AI's applications in smart government. To maximize the future impact of community service activities, it is recommended to develop more comprehensive materials, provide continuous training, engage additional partners, and conduct regular evaluations and improvements. By taking these steps, community service initiatives can generate greater benefits for participants and the wider community